Mica paper processing liquid, fireproof mica plate for energy storage battery pack and preparation method thereof
By using mica paper treatment solutions A and B in specific proportions, combined with impregnation and interlocking coating processes, fire-resistant mica boards with excellent aging resistance were prepared, solving the problem of easy aging of traditional mica boards in energy storage power station environments and achieving high mechanical strength and low water absorption.
Patent Information
- Application Number
- CN202411400541.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-10-09
AI Technical Summary
Traditional mica panels are prone to aging due to moisture in energy storage power station environments and cannot meet the requirements for aging resistance.
Fireproof mica boards are prepared by using mica paper treatment solutions A and B with specific ratios. Treatment solution A is composed of high-temperature resistant silicone rubber, chloroprene rubber, diaryl secondary amine, and silane coupling agent, while treatment solution B is composed of acrylic resin, aluminum hydroxide, titanium dioxide, hexadecyltrimethylammonium bromide, and coupling agent.
It improves the aging resistance of mica sheets, reduces water absorption, enhances mechanical strength and toughness, and avoids defects such as bubbles, delamination, and pores during the molding process.
Smart Images

Figure BDA0005075155570000051 
Figure BDA0005075155570000061 
Figure BDA0005075155570000071
Abstract
Description
Technical Field
[0001] This application relates to the technical field of mica materials, specifically to a mica paper treatment liquid, a fireproof mica board for energy storage battery packs, and a method for preparing the same. Background Technology
[0002] Currently, the fire-retardant materials used in the battery packs of energy storage power stations mainly use mica boards. Traditional mica boards are made by laminating multiple layers of mica paper with silicone resin to achieve the required thickness. However, the performance of mica materials is greatly affected by the environment and they are prone to moisture absorption, which makes them unable to meet the environmental requirements of energy storage power stations and the requirements of energy storage power stations as they age. Summary of the Invention
[0003] To improve the aging resistance of mica paper, this application provides a mica paper treatment solution, a fireproof mica board for energy storage battery packs, and a method for preparing the same.
[0004] In a first aspect, this application provides a mica paper treatment solution, including treatment solution A and treatment solution B; The treatment solution A comprises the following components in parts by weight: 20-30 parts of high-temperature resistant silicone rubber, 10-20 parts of chloroprene rubber, 5-15 parts of diaryl secondary amine, and 0.10-0.32 parts of silane coupling agent; The treatment solution B comprises the following components in parts by weight: 30-40 parts acrylic resin, 6-12 parts aluminum hydroxide, 8-12 parts titanium dioxide, 4-6 parts hexadecyltrimethylammonium bromide, and 0.2-0.4 parts coupling agent.
[0005] Mica possesses good high-temperature resistance and insulation properties. In treatment solution A, the high-temperature resistant silicone rubber has a very flexible main chain with weak intermolecular forces, providing suitable viscosity, low surface tension, low surface energy, and strong film-forming ability. This results in a good apparent structure after the mica sheet is formed. Furthermore, silicone rubber and chloroprene rubber exhibit good heat and cold resistance, good chemical stability, high rigidity and toughness, and good mechanical strength, while also increasing the toughness of the mica system. Diaryl secondary amines have anti-aging properties, and coupling agents provide excellent binding force. In treatment solution B, aluminum hydroxide and titanium dioxide fill the pores between the fine particles in treatment solution B, and interact with other substances in treatment solution B to increase the viscosity and toughness of the system, while also improving the aging resistance of the mica sheet.
[0006] Preferably, in the treatment solution A, the diaryl secondary amine is composed of a mixture of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine and N-cyclohexyl-N-phenyl-p-phenylenediamine in a weight ratio of 9:1-3; the silane coupling agent is selected from any one or more of vinyl silane coupling agents, amino silane coupling agents, and methacryloxysilane coupling agents; and the high-temperature resistant silicone is selected from one or more of SH-9501, SH-9602, and SH-5202S.
[0007] Preferably, in the treatment solution B, the coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, propyltriethoxysilane, mercaptopropyltriethoxysilane, ethylenediaminepropyltriethoxysilane, ethylenediaminepropylmethyldimethoxysilane, vinyltriacetoxysilane, or vinyltriethoxysilane.
[0008] Preferably, in the treatment solution B, the coupling agent is composed of a mixture of γ-methacryloyloxypropyltrimethoxysilane and ethylenediaminepropylmethyldimethoxysilane in a weight ratio of 1:0.1-0.5.
[0009] Preferably, the treatment solution A is prepared by weighing the corresponding weights of each raw material component and stirring for ≥60 minutes at a stirring speed ≥500 rpm to obtain the treatment solution A.
[0010] During the testing of the preparation method for treatment solution A, the applicant found that the uniformity was poor when the stirring speed was below 500 rpm and when the stirring time was below 60 min. Therefore, this application controls the parameters within the above-mentioned ranges.
[0011] Preferably, the treatment solution B is prepared by weighing the corresponding weights of each raw material component, placing them in a reaction vessel, and stirring for ≥30 minutes at a temperature of 50-70℃ and a stirring speed of ≥80 rpm to obtain the treatment solution B.
[0012] During the testing of the preparation method for treatment solution B, the applicant found that when the reactor temperature was below 50°C, the film-forming effect was poor; when the reactor temperature was above 70°C, solidified substances appeared in the mixture; when the stirring speed was below 80 rpm, the mixing was uneven and the coating was uneven; when the stirring time was below 30 min, the mixing was uneven and the coating was uneven. Therefore, this application controls the parameters within the above-mentioned ranges.
[0013] Furthermore, the temperature of the reactor is 55-65°C.
[0014] During the testing of the preparation method for treatment solution B, the applicant found that when the reactor temperature was 50-55℃ or 65-70℃, the prepared fireproof mica board exhibited high water absorption (0.39-0.42%) after aging tests, which reduced its application performance. Therefore, this application controls the reactor temperature parameter within the range of 55-65℃.
[0015] Secondly, this application provides a fireproof mica board for energy storage battery packs, which is prepared by impregnating phlogopite paper with the aforementioned mica paper treatment solution.
[0016] Thirdly, this application provides a method for preparing the fire-resistant mica plate for the above-mentioned energy storage battery pack, specifically including the following steps: Phlogopite paper is impregnated in the treatment solution A using a laminator with a speed of 5-7 m / min. After lamination, the phlogopite paper is hot-pressed using a press to obtain a pretreated mica board. The hot-pressing parameters are: hot-pressing temperature 160-200℃, pressure 1.8-2.2 MPa, and hot-pressing time ≥20 min. The treatment liquid B is applied to the surface of the pretreated mica board by a gap coating method, with the gap being 0.1±0.02mm. After drying, the fireproof mica board for the energy storage battery pack is obtained. The drying parameters are as follows: drying is carried out in three zones, each zone is 7-9m long, the drying speed is 7-10m / min, the temperature of zone 1 is 50-60℃, the temperature of zone 2 is 100-120℃, and the temperature of zone 3 is 130-150℃.
[0017] During the experimental preparation of fire-resistant mica sheets, the applicant found the following during the impregnation process of the mica sheets in treatment solution A: when the speed of the laminating machine was below 5 m / s, the amount of adhesive (treatment solution A) applied was high, resulting in air bubbles during hot pressing; when the speed of the laminating machine was above 7 m / s, the amount of adhesive (treatment solution A) applied was low, resulting in delamination after hot pressing. When the hot pressing temperature was above 200℃, the mica sheets shed powder; when the hot pressing temperature was below 160℃, the adhesion between the mica layers was poor. When the pressure was above 2.2 MPa, the mica sheets deformed; when the pressure was below 1.8 MPa, the adhesion between the mica layers was poor. When the hot pressing time was below 20 min, the adhesion between the mica layers was poor.
[0018] During the testing of the preparation method for fire-resistant mica panels, the applicant discovered the following during the coating process with treatment liquid B: when the vehicle speed was below 5 m / min, the coating failed to cure; when the vehicle speed was above 7 m / min, bubbles appeared on the coating surface. When the temperature in drying zone one was below 50°C, the solvent in the adhesive could not be dried; when the temperature in zone one was above 60°C, bubbles appeared on the surface. When the temperature in zone two was below 100°C, the coating liquid failed to cure; when the temperature in zone two was above 120°C, bubbles appeared on the surface. When the temperature in zone three was below 130°C, the surface became tacky; when the temperature in zone three was above 150°C, cracks appeared.
[0019] Preferably, the hot pressing parameters are: hot pressing temperature of 170-190℃, pressure of 1.9-2.1 MPa, and hot pressing time of ≥20 min.
[0020] During the experimental preparation of fire-resistant mica sheets, the applicant discovered that when the mica sheets were impregnated in treatment solution A, the water absorption of the mica sheets after aging tests was relatively high at hot-pressing temperatures of 160-170℃ or 190-200℃. Similarly, the water absorption of the mica sheets after aging tests was also relatively high at pressures of 1.8-1.9 MPa or 2.1-2.2 MPa. Therefore, this application controls the hot-pressing temperature and pressure parameters within the aforementioned ranges.
[0021] Preferably, the drying parameters are as follows: drying is carried out in three zones, each zone is 7.5-8.5m long, the drying speed is 8-9m / min, the temperature of the first zone is 53-58℃, the temperature of the second zone is 105-115℃, and the temperature of the third zone is 135-145℃.
[0022] During the preparation method test of fireproof mica board, the applicant found that when the length of each zone was controlled to be 7.5-8.5m, the drying speed was 8-9m / min, the temperature of zone 1 was 53-58℃, the temperature of zone 2 was 105-115℃, and the temperature of zone 3 was 135-145℃, the water absorption of the mica board after aging test was relatively small. That is, this application controls the temperature of each zone during drying to the above range, which further improves the aging resistance of the mica board.
[0023] In summary, the technical solution of this application has the following effects: This application uses specific weight parts of high-temperature resistant silicone rubber, chloroprene rubber, diaryl secondary amine, and silane coupling agent as raw material components of treatment liquid A, and specific weight parts of acrylic resin, aluminum hydroxide, titanium dioxide, hexadecyltrimethylammonium bromide, and coupling agent as raw material components of treatment liquid B. Phlogopite paper is impregnated in the above-mentioned treatment liquid A through a gluing machine, and then mica board is produced using a press. Then, an anti-aging coating (treatment liquid B) is applied to the surface of the mica board through a seam coating method. After drying, the coating is prepared. The resulting fireproof mica board has strong voltage resistance, bending strength, low water absorption, and excellent aging resistance.
[0024] The fireproof mica board preparation method provided in this application is simple to operate and reduces production costs. By controlling the types and amounts of raw materials and the specific process parameters in the preparation process, it avoids defects such as bubbles, delamination, pores, embrittlement, cracks, powdering, unevenness, and orange peel appearance during the molding process of fireproof mica board.
[0025] This application further improves the aging resistance of fireproof mica boards by screening the types of diaryl secondary amines in treatment solution A and the types of coupling agents in treatment solution B. Attached Figure Description
[0026] Figure 1 This is a process flow diagram of the preparation method of fireproof mica plate for energy storage battery pack in the embodiments of this application. Detailed Implementation
[0027] The present application will be further described in detail below with reference to embodiments, comparative examples and performance test results. These embodiments should not be construed as limiting the scope of protection claimed in this application. Example
[0028] Examples 1-19 Examples 1-19 provide a fireproof mica plate for an energy storage battery pack and its preparation method.
[0029] The difference between the above embodiments is that the amounts of each component in treatment solution A and treatment solution B are different, as shown in Table 1.
[0030] The process flow diagram of the preparation method of the fireproof mica plate for the energy storage battery pack in the above embodiments is as follows: Figure 1 As shown, the specific steps are as follows: The preparation method of treatment solution A is as follows: according to Table 1, weigh the corresponding weights of each raw material component, high-temperature resistant silicone SH-9602, chloroprene rubber, diaryl secondary amine (composed of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine and N-cyclohexyl-N-phenyl-p-phenylenediamine in a weight ratio of 9:2), and silane coupling agent (KH-560). Stir at a stirring speed of 600 rpm for 80 min to prepare mica paper treatment solution.
[0031] The preparation method of treatment solution B is as follows: according to Table 1, weigh the corresponding weights of each raw material component, acrylic resin, aluminum hydroxide, titanium dioxide, hexadecyltrimethylammonium bromide, and coupling agent (composed of γ-methacryloyloxypropyltrimethoxysilane and ethylenediaminepropylmethyldimethoxysilane in a weight ratio of 1:0.3), put them into a reaction vessel, and stir for 40 min at a temperature of 60℃ and a stirring speed of 100 rpm to prepare treatment solution B.
[0032] Phlogopite paper (model P506, purchased from Pingjiang Weipai Mica Insulation Materials Co., Ltd.) was impregnated in treatment solution A using a gluing machine at a speed of 6 m / min. After gluing, the phlogopite paper was hot-pressed using a press to obtain a pretreated mica board. The hot-pressing parameters were: hot-pressing temperature 180℃, pressure 2.0 MPa, and hot-pressing time 25 min.
[0033] Treatment liquid B is applied to the surface of the pretreated mica board by a gap coating method, and then dried to obtain a fireproof mica board for energy storage battery pack. The gap is 0.11mm. The drying parameters are as follows: drying is carried out in three zones, each zone is 8m long, the drying speed is 8.5m / min, the temperature of zone 1 is 55℃, the temperature of zone 2 is 110℃, and the temperature of zone 3 is 140℃.
[0034] Table 1. Amounts of each component in treatment solution A and treatment solution B in Examples 1-19 Examples 20-23 Examples 20-23 respectively provide a fireproof mica plate for an energy storage battery pack and its preparation method.
[0035] The difference between the above embodiments and Embodiment 1 is that the types of diaryl secondary amines in treatment solution A are different, as detailed below.
[0036] In Example 20: the diaryl secondary amine is composed of N-phenyl-α-naphthylamine and N-cyclohexyl-N-phenyl-p-phenylenediamine in a weight ratio of 9:2.
[0037] In Example 21: the diaryl secondary amine is composed of a mixture of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine and N-cyclohexyl-N-phenyl-p-phenylenediamine in a weight ratio of 2:9.
[0038] In Example 22: the diaryl secondary amine is composed of a mixture of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine and N-cyclohexyl-N-phenyl-p-phenylenediamine in a weight ratio of 9:1.
[0039] In Example 23: the diaryl secondary amine is composed of a mixture of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine and N-cyclohexyl-N-phenyl-p-phenylenediamine in a weight ratio of 9:3.
[0040] The above embodiments are the same as those in Embodiment 1 in terms of the preparation methods of other raw materials and mica boards.
[0041] Examples 24-27 Examples 24-27 provide a fireproof mica plate for an energy storage battery pack and its preparation method.
[0042] The difference between the above embodiments and Embodiment 1 is that the type of coupling agent in the treatment solution B is different, as detailed below.
[0043] In Example 24: the coupling agent is composed of a mixture of γ-methacryloyloxypropyltrimethoxysilane and propyltriethoxysilane in a weight ratio of 1:0.3.
[0044] In Example 25: The coupling agent is composed of a mixture of γ-methacryloyloxypropyltrimethoxysilane and ethylenediaminepropylmethyldimethoxysilane in a weight ratio of 0.3:1.
[0045] In Example 26: The coupling agent is composed of a mixture of γ-methacryloyloxypropyltrimethoxysilane and ethylenediaminepropylmethyldimethoxysilane in a weight ratio of 1:0.1.
[0046] In Example 27: The coupling agent is composed of a mixture of γ-methacryloyloxypropyltrimethoxysilane and ethylenediaminepropylmethyldimethoxysilane in a weight ratio of 1:0.5.
[0047] The above embodiments are the same as those in Embodiment 1 in terms of the preparation methods of other raw materials and mica boards.
[0048] Comparative Example Comparative Examples 1-18 Comparative Examples 1-18 each provide a mica plate and its preparation method.
[0049] The difference between the above comparative example and Example 1 is that the amounts of each component in treatment solution A and treatment solution B are different, as shown in Table 2.
[0050] Table 2 shows the dosage of each component in treatment solution A and treatment solution B in Comparative Examples 1-18. The preparation methods of the mica plates in the above comparative examples and in Example 1 are the same.
[0051] Comparative Examples 19-22 Comparative Examples 19-22 each provide a mica board and its preparation method.
[0052] The differences between the above comparative examples and Example 1 are as follows.
[0053] In Comparative Example 19, an equal amount of methyl vinyl silicone rubber was used instead of chloroprene rubber.
[0054] In Comparative Example 20, an equal amount of polyimide resin was used instead of acrylic resin.
[0055] In Comparative Example 21, an equal amount of aluminum hydroxide was used instead of titanium dioxide.
[0056] In Comparative Example 22, aluminum hydroxide was replaced with an equal amount of aluminum silicate.
[0057] The preparation methods of the other raw materials and mica boards in the above comparative examples are the same as those in Example 1.
[0058] Performance testing (1) Appearance characteristics: Observe whether there are defects on the surface of the mica board during the preparation process and the prepared mica board product.
[0059] (2) Voltage withstand performance: The voltage withstand performance of the mica board was tested using a voltage withstand tester in accordance with the test method of GB / T5019.2-2009.
[0060] (3) Bending strength: The bending strength performance of the mica board is tested using a bending strength tester.
[0061] (4) Water absorption rate: Soak the mica board in water for 60 minutes, take out the absorbent paper and wipe it dry gently. Use an electronic balance to test the water absorption rate of the mica board.
[0062] (5) Aging resistance: The mica board was exposed to a double-lamp enclosed carbon arc for 720 hours to test its voltage resistance, bending strength and water absorption.
[0063] Test results are shown in Table 3.
[0064] Table 3 Performance test results of mica plates in Examples 1-27 and Comparative Examples 1-22 Experiments have shown that the mica board prepared using the technical solution of this application is intact and without defects during the preparation process and on the surface of the prepared mica board. Furthermore, after aging tests, the mica board sample remains intact and without defects.
[0065] In Comparative Example 1, when the amount of high-temperature resistant silicone in treatment solution A is less than 20 parts by weight, the mica board layers delaminate (the mica board is made of multiple layers of mica paper).
[0066] In Comparative Example 2, when the amount of high-temperature resistant silicone in treatment solution A exceeded 30 parts by weight, bubbles appeared on the surface of the mica board.
[0067] In Comparative Example 3, when the amount of chloroprene rubber in treatment solution A was less than 10 parts by weight, the mica sheets delaminated after aging.
[0068] In Comparative Example 4, when the amount of chloroprene rubber in treatment solution A was higher than 20 parts by weight, pores appeared between the mica layers.
[0069] In Comparative Example 5, when the amount of diaryl secondary amine in treatment solution A was less than 5 parts by weight, the mica board became brittle after aging.
[0070] In Comparative Example 6, when the amount of diaryl secondary amine in treatment solution A was higher than 15 parts by weight, pores appeared between the mica layers.
[0071] In Comparative Example 7, when the silane coupling agent in treatment solution A was less than 0.10 parts by weight, the mica paper delaminated after curing.
[0072] In Comparative Example 9, when the amount of acrylic resin in treatment solution B was less than 30 parts by weight, the surface film formation was poor.
[0073] In Comparative Example 10, when the acrylic resin content in treatment solution B exceeded 40 parts by weight, cracks appeared in the coating after drying.
[0074] In Comparative Example 11, when the aluminum hydroxide content in treatment solution B was less than 6 parts by weight, the coating cracked after aging.
[0075] In Comparative Example 12, when the aluminum hydroxide content in treatment solution B was higher than 12 parts by weight, powder was shed from the surface after drying.
[0076] In Comparative Example 13, when the titanium dioxide content in treatment solution B was less than 8 parts by weight, the coating surface exhibited poor weather resistance.
[0077] In Comparative Example 14, when the titanium dioxide content in treatment solution B was higher than 12 parts by weight, the coating surface was uneven and orange peel-like appeared.
[0078] In Comparative Example 15, when the amount of cetyltrimethylammonium bromide in treatment solution B was less than 4 parts by weight, the coating lost its gloss after aging.
[0079] When the amount of hexadecyltrimethylammonium bromide in treatment solution B in Comparative Example 16 was higher than 6 parts by weight, white powder appeared on the coating surface.
[0080] In Comparative Example 17, when the coupling agent in treatment solution B was less than 0.2 parts by weight, the coating peeled off.
[0081] In Comparative Example 18, when the coupling agent in treatment solution B was higher than 0.4 parts by weight, solidified products appeared in the mixture.
[0082] Based on Table 2, by comparing the test results of Examples 1-27 with those of Comparative Examples 8 and 19-24, it can be seen that this application uses high-temperature resistant silicone, chloroprene rubber, diaryl secondary amine, and silane coupling agent as raw material components of treatment liquid A, and acrylic resin, aluminum hydroxide, titanium dioxide, hexadecyltrimethylammonium bromide, and coupling agent as raw material components of treatment liquid B. Phlogopite paper is impregnated in the above-mentioned treatment liquid A through a gluing machine, and then mica board is produced using a press. Then, an anti-aging coating (treatment liquid B) is applied to the surface of the mica board through a seam coating method. After drying, the resulting fireproof mica board has strong voltage resistance, bending strength, low water absorption, and excellent aging resistance.
[0083] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a fire-resistant mica plate for an energy storage battery pack, characterized in that, Specifically, the following steps are included: Phlogopite paper is impregnated in treatment solution A using a laminator with a speed of 5-7 m / min. After lamination, the phlogopite paper is hot-pressed using a press to obtain a pretreated mica board. The hot-pressing parameters are as follows: hot-pressing temperature is 160-200℃, pressure is 1.8-2.2Mpa, and hot-pressing time is ≥20min; treatment liquid B is coated on the surface of the pretreated mica board by a gap coating method, with a gap of 0.1±0.02mm, and then dried to obtain the fireproof mica board for the energy storage battery pack; the drying parameters are as follows: drying is divided into three zones, each zone is 7-9m long, the drying speed is 7-10m / min, the temperature of zone one is 50-60℃, the temperature of zone two is 100-120℃, and the temperature of zone three is 130-150℃; The treatment solution A comprises the following components in parts by weight: 25-30 parts of high-temperature resistant silicone rubber, 15-20 parts of chloroprene rubber, 10-15 parts of diaryl secondary amine, and 0.15-0.32 parts of silane coupling agent; The treatment solution B comprises the following components in parts by weight: 35-40 parts acrylic resin, 9-12 parts aluminum hydroxide, 10-12 parts titanium dioxide, 5-6 parts hexadecyltrimethylammonium bromide, and 0.3-0.4 parts coupling agent; In the treatment solution A, the diaryl secondary amine is composed of a mixture of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine and N-cyclohexyl-N-phenyl-p-phenylenediamine in a weight ratio of 9:1-3. In the treatment solution B, the coupling agent is composed of a mixture of γ-methacryloyloxypropyltrimethoxysilane and ethylenediaminepropylmethyldimethoxysilane in a weight ratio of 1:0.1-0.
5.
2. The method for preparing fireproof mica sheet for energy storage battery packs according to claim 1, characterized in that, The preparation method of the treatment solution A is as follows: weigh the corresponding weight of each raw material component, stir for ≥60 min at a stirring speed ≥500 rpm, and the treatment solution A is prepared.
3. The method for preparing fireproof mica sheet for energy storage battery packs according to claim 1, characterized in that, The preparation method of the treatment solution B is as follows: weigh the corresponding weights of each raw material component, put them into a reaction vessel, and stir for ≥30 minutes at a temperature of 50-70℃ and a stirring speed of ≥80rpm to obtain the treatment solution B.
4. The method for preparing the fireproof mica plate for the energy storage battery pack according to claim 1, characterized in that, The hot pressing parameters are: hot pressing temperature 170-190℃, pressure 1.9-2.1 MPa, and hot pressing time ≥20 min.
5. The method for preparing the fireproof mica plate for the energy storage battery pack according to claim 1, characterized in that, The drying parameters are as follows: drying is divided into three zones, each zone is 7.5-8.5m long, the drying speed is 8-9m / min, the temperature of zone one is 53-58℃, the temperature of zone two is 105-115℃, and the temperature of zone three is 135-145℃.
6. A fireproof mica sheet for an energy storage battery pack prepared by the method according to any one of claims 1-5.
Citation Information
Patent Citations
High-strength and high-heat-insulation fiber composite fireproof mica plate
CN116330769A
New energy automobile waterproof mica plate and preparation method thereof
CN117153504A
